2022
DOI: 10.3390/f13060926
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Herbicide Clopyralid and Imazamox on Dehydrogenase Enzyme in Soil of Regenerated Pedunculate Oak Forests

Abstract: Clopyralid and imazamox are successfully used for weed control during the first years of regeneration of pedunculate oak forests. Hence, the question that arises is how these herbicides affect microorganisms, especially the activity of dehydrogenase enzyme, when they reach the soil. Two study sites were selected in regenerated pedunculate oak forests, and the two herbicides were applied in two doses that are used for weed control (clopyralid, 100 g a.i. ha−1 and 120 g a.i. ha−1; imazamox, 40 g a.i. ha−1 and 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…In the currently available literature, we have not found any studies dealing with damage to subsequent crops using the herbicide pyroxsulam, but there are several studies looking at damage to strawberry by the herbicide clopyralid residues (Hunnicutt et al, 2013;Sharpe et al, 2018). Clopyralid is an auxin-type herbicide, and it is more selective than some other auxin herbicides, such as picloram, triclopyr or 2,4-D (Vasic et al, 2022). First study (Hunnicutt et al, 2013) evaluated three different strawberry cultivars, namely 'Treasure', 'Festival' and 'Camino Real', for sensitivity to clopyralid at spray application doses of 0, 45, 66, 132, 195 and 814 g.ha -1 .…”
Section: Discussionmentioning
confidence: 99%
“…In the currently available literature, we have not found any studies dealing with damage to subsequent crops using the herbicide pyroxsulam, but there are several studies looking at damage to strawberry by the herbicide clopyralid residues (Hunnicutt et al, 2013;Sharpe et al, 2018). Clopyralid is an auxin-type herbicide, and it is more selective than some other auxin herbicides, such as picloram, triclopyr or 2,4-D (Vasic et al, 2022). First study (Hunnicutt et al, 2013) evaluated three different strawberry cultivars, namely 'Treasure', 'Festival' and 'Camino Real', for sensitivity to clopyralid at spray application doses of 0, 45, 66, 132, 195 and 814 g.ha -1 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that fumigants tested can reduce soil DHase activity, but this effect is transient. This can be attributed to the ability of microorganisms to overcome the stress caused by the chemicals by developing the capability to utilize chemicals as a nutrient source and proliferating in such an environment (Vasic et al, 2022).…”
Section: Effect Of Tested Fumigants On Dhase Activitymentioning
confidence: 99%
“…One of the most significant problems during the regeneration of oak forests is the elimination of negative weed impact [1,2]. Weed management is very important in regenerated oak forests, especially when seedlings are young; then, seedlings have a low chance to compete with more vigorous and fast-growing weeds for light, water, and nutrients [3].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, microorganisms can degrade herbicides and use them as sources of biogenic elements, or they can be toxic to microorganisms, reducing their numbers and activity [15]. Investigations which were conducted [2,16] showed that when herbicides were applied at optimal doses, as recommend by specialists, the changes they generated in the microbiological activity of soil were transitory. Moreover, managing weeds in early spring implies fewer weeds in the regenerated area during the vegetation season, improved nutrient and water uptake by the oak seedlings, and less manual labour required later in the season when it comes time to perform some other jobs.…”
Section: Introductionmentioning
confidence: 99%